Lack of sex-specific differences in the associations between the dimensions of great vessels and exercise performance in amateur cyclists - Pytka, Michał J.; Domin, Remigiusz A.; Żołyński, Mikołaj S.; Niziński, Jan; Krauze, Tomasz; Więckowska, Barbara; Wykrętowicz, Andrzej; Guzik, Przemysław (PLOS ONE, 2024)
Background Endurance training enhances exercise capacity and triggers cardiovascular adaptations in both males and females. We investigated the relationship between the dimensions of great vessels and exercise capacity in amateur cyclists while considering sex differences. Methods Using resting transthoracic echocardiography, we measured the dimensions of the main pulmonary artery (PA), aorta, and inferior vena cava (IVC) in 190 participants, who subsequently underwent a cardiopulmonary exercise test (CPET) until exhaustion. Results The mean age of study participants was 30 years. Males (71%) exhibited a larger aortic annulus (approximately 3.5 mm, p<0.0001) and PA diameter (2.4 mm, p<0.0001) than females. No significant sex differences were found in expiratory or inspiratory IVC diameters. Males achieved greater peak exercise capacity, including workload, O2 consumption (VO2), and O2 pulse. Aortic and PA dimensions showed strong correlations with energy expenditure, workload, VO2, and O2 pulse. However, these correlations weakened when analyzed separately by sex. Multivariate linear regression revealed associations between CPET results, vessels size, and sex, with sex differences observed only in the intercepts—not in interactions between sex and vessels size. Despite males having better CPET results and larger vessels, the relationships between peak exercise capacity parameters and vessel dimensions were similar in both sexes. Conclusion Larger vessel dimensions (of the aorta, PA, and IVC) were associated with greater peak exercise capacity in amateur cyclists, with no significant sex differences in these associations.